-2(x+1)-6=(6x-2)+3

Simple and best practice solution for -2(x+1)-6=(6x-2)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x+1)-6=(6x-2)+3 equation:


Simplifying
-2(x + 1) + -6 = (6x + -2) + 3

Reorder the terms:
-2(1 + x) + -6 = (6x + -2) + 3
(1 * -2 + x * -2) + -6 = (6x + -2) + 3
(-2 + -2x) + -6 = (6x + -2) + 3

Reorder the terms:
-2 + -6 + -2x = (6x + -2) + 3

Combine like terms: -2 + -6 = -8
-8 + -2x = (6x + -2) + 3

Reorder the terms:
-8 + -2x = (-2 + 6x) + 3

Remove parenthesis around (-2 + 6x)
-8 + -2x = -2 + 6x + 3

Reorder the terms:
-8 + -2x = -2 + 3 + 6x

Combine like terms: -2 + 3 = 1
-8 + -2x = 1 + 6x

Solving
-8 + -2x = 1 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-8 + -2x + -6x = 1 + 6x + -6x

Combine like terms: -2x + -6x = -8x
-8 + -8x = 1 + 6x + -6x

Combine like terms: 6x + -6x = 0
-8 + -8x = 1 + 0
-8 + -8x = 1

Add '8' to each side of the equation.
-8 + 8 + -8x = 1 + 8

Combine like terms: -8 + 8 = 0
0 + -8x = 1 + 8
-8x = 1 + 8

Combine like terms: 1 + 8 = 9
-8x = 9

Divide each side by '-8'.
x = -1.125

Simplifying
x = -1.125

See similar equations:

| 0=6-2y | | 20x+30y+50z=240 | | 14-l=-46 | | 8c+-15=-47 | | 9r-34=29 | | 3a-15+4-2a=-17 | | x+4+2x+2+3x+10=18 | | 6x-2(x-6)=4(x+1)+2 | | 9*(3+4)= | | 1.5x+3y-z=-8 | | x-x*0.1=86.96 | | -5(1)=8+4m | | x(5+x)=(x*x)+3x+1 | | 12q-4=32 | | 2(3x-4)+5-4x=11 | | 24x+1.8-x+3=16-1 | | 16x=.6x | | 0.8(x-5)=0.4x-20 | | -Rx+5y=-T | | 7x+-5=4x+4 | | 24x+1*8-x+3=16-1 | | f(x)=x(x+1)(x-6) | | -5(0)=8+4m | | (M+3)(m-4)= | | 56+12x=8+8x | | D=2abc | | 1.5r+15=45r | | -3X+10+4X=13 | | 2ax=10a-3ax | | 8y+8=7y-12 | | 4t-2=33-3y | | 7m+38=5m-16 |

Equations solver categories